Moderate associated fetal ventriculomegaly: prenatal diagnosis - Albu, Cristina Crenguta; Albu, Dinu Florin; Albu, Stefan Dimitrie (International Journal of Research in Medical Sciences, 2020)
Ventriculomegaly (VM) is a descriptive term, indicating the enlargement of the ventricles of the brain. We present the case of a 32-year-old primiparous women, at 18 weeks of pregnancy, who was referred in our clinic for a routine prenatal ultrasound examination. The ultrasound scan highlighted a single malformed fetus with several major abnormalities of the fetal head: hypoplastic nasal bone, agenesis of corpus callosum, choroid plexus hyperplasia, solid hypoechoic mass on the external wall of the left ventricle, no visible cavum septum pellucidum, third ventricle visible, moderately enlarged and VM with evolution to bilateral hydrocephalus. The parents were informed about the major severity of anomalies and decide to terminate the pregnancy. Prenatal ultrasound examination was decisive in the early prenatal diagnosis and optimized management of the malformed fetus with VM.